Long-term Virological and Adherence Outcomes to Antiviral Treatment in a 4-year Cohort Chronic HBV Study. Issue 8 (November 2019) - Abreu, Rodrigo M; Bassit, Leda C; Tao, Sijia; Jiang, Yong; Ferreira, Aline S; Hori, Patrícia CA; Ganova-Raeva, Lilia M; Khudyakov, Yury; Schinazi, Raymond F; Carrilho, Flair J; Ono, Suzane K
Background: Chronic hepatitis B (CHB) treatment adherence has been poorly studied worldwide. We evaluated long-term virological and adherence outcomes to antiviral treatment in CHB patients. Methods: A prospective 183 Brazilian CHB patient cohort treated with monotherapy or combination adefovir dipivoxil, entecavir, lamivudine and/or tenofovir disoproxil fumarate was studied in a reference tertiary centre. Treatment adherence was evaluated by a validated questionnaire named 'Assessment of Adherence to Antiviral Therapy Questionnaire' (CEAT-HBV) within three yearly periods (2010/2011, 2013/2014 and 2014/2015). Results: CEAT-HBV identified 43% (79/183) patients with non-adherence to antiviral treatment and among them, 67% (53/79) were viral load positive. The main causes associated with non-response to antiviral treatment were drug resistance variants followed by non-adherence, insufficient treatment duration and other causes. Single-dose pharmacokinetics demonstrated 35% (23/65) antiviral non-adherence. 2 years after the first assessment, the CEAT-HBV indicated that 71% (101/143) of subjects adhered to treatment (per-protocol population). However, 21% (40/183) of the patients could not be evaluated and were excluded. The main reasons for exclusion were death (20/183), 11 out 20 deaths due to hepatocellular carcinoma. HBV booklet was used for medical education. The third CEAT-HBV assessment (2014/2015) showed that 83% (112/135) patients were compliant with treatment adherence (per-protocol population). Long-term evaluation showed that adherence rate based on CEAT-HBV continue to increase after 4-years ( P <0.001). Conclusions: The results highlight the importance of CHB therapy adherence assessment monitoring. Long-term adherence outcomes were dynamic and it is possible to increase the migration rate to adherence/HBV-DNA-negative group.